RO-MAN 2008 - The 17th IEEE International Symposium on Robot and Human Interactive Communication 2008
DOI: 10.1109/roman.2008.4600728
|View full text |Cite
|
Sign up to set email alerts
|

Understanding social robots: A user study on anthropomorphism

Abstract: Abstract-Anthropomorphism is one of the keys to understand the expectations people have about social robots. In this paper we address the question of how a robot's actions are perceived and represented in a human subject interacting with the robot and how this perception is influenced only by the appearance of the robot. We present results of an interaction-study in which participants had to play a version of the classical Prisoners' Dilemma Game (PDG) against four opponents: a human partner (HP), an anthropom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
58
2
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(67 citation statements)
references
References 24 publications
5
58
2
2
Order By: Relevance
“…The familiarity thesis [6] would support the idea that the human first projects onto the robot mental models of similar agents he/she is already familiar with (ranging from animals to human adults, to pets and children).…”
Section: B) Cognitive Interpretationsmentioning
confidence: 99%
“…The familiarity thesis [6] would support the idea that the human first projects onto the robot mental models of similar agents he/she is already familiar with (ranging from animals to human adults, to pets and children).…”
Section: B) Cognitive Interpretationsmentioning
confidence: 99%
“…For instance, Premack and Premack [33] demonstrated that people will anthropomorphize simple animated 2-dimensional shapes and attribute intentions to them if they move appropriately. Furthermore, mechanical devices such as robots are more readily anthropomorphized when they possess human-like faces and bodies [11,16].…”
Section: Must Intentions Be Attributed To a Robot?mentioning
confidence: 99%
“…The two robot types have contrasting attributesbiologically inspired robot is being developed with life-like multi-functions whereas the functionally designed robots aim for specialized functionality for certain use. Several researches have been done in comparison of the two robot types, and the results showed that people perceived familiarity, intelligence and acceptance of the robots differently [2], [3]. Likewise, Lee et al [5] conducted comparative studies between human-like robot and product-like robots both in Korea and Japan to examine the impact of robot design types and cultural aspects on people's acceptance of a robot.…”
Section: Introductionmentioning
confidence: 99%